The Limited Nuclear Weapon Free Zone in Northeast Asia: Is It Feasible? - Seongwhun, Cheon (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.31 Mongolian Journal of International Affairs No.14 2007 pp.106-115